Enhancing Vocational Educational Quality through Training for Teachers and ABK at SLB Kristen Pelangi Kasih - Siti Zahro; Christabel Annora Paramita Parung; Kenny Hartanto; Indra Jaya Gunawan; Gabriella Haldis Adriani; Dewi Anggraini Tjandra (GUYUB: Journal of Community Engagement, 2025)
Children with special needs need vocational education in fashion design to become independent after graduation. This is because special needs schools (SLB) have a low understanding of the quality of learning, skills development, and intellectual property rights (HKI) for their creations, making them marketable. This Community Service Program (PkM) aimed to enhance the quality of the fashion design vocational education program through fashion skills training and intellectual property rights training for teachers and children with special needs (ABK) to prepare students' independence after graduation from SLB Kristen Pelangi Kasih, Lumajang Regency. The implementation adopted a service-learning approach, which consisted of several stages: problem identification, priority setting, timeline planning, implementation, and evaluation. Data were collected through observation, questionnaires, unstructured interviews, and documentation, and were analyzed descriptively. The results showed that fashion design skills, through training in painting on fabric marbelling, sewing, and cowhide painting, were successfully implemented, and the IPR training for student work provided valuable training for participating teachers. The evaluation showed that 80%-100% of participants stated that the training provided new experiences for them and positively contributed to enhancing the creativity of children with special needs at the SLB Kristen Pelangi Kasih. Ultimately, it can be concluded that the SLB's challenges related to developing student independence can be addressed through vocational skills training supported by IPR for their products.